The link between abnormalities of calcium handling proteins and catecholaminergic polymorphic ventricular tachycardia - Ding-Jyun Lin; Wen-Sen Lee; Yu-Chung Chien; Tsung-Yu Chen; Kun-Ta Yang (Tzu Chi Medical Journal)
Catecholaminergic polymorphic ventricular tachycardia (CPVT), a rare autosomal dominant or recessive disease, usually results in syncope or sudden cardiac death. Most CPVT patients do not show abnormal cardiac structure and electrocardiogram features and symptoms, usually onset during adrenergically mediated physiological conditions. CPVT tends to occur at a younger age and is not easy to be diagnosed and managed. The main cause of CPVT is associated with mishandling Ca2+ in cardiomyocytes. Intracellular Ca2+ is strictly controlled by a protein located in the sarcoplasm reticulum (SR), such as ryanodine receptor, histidine-rich Ca2+-binding protein, triadin, and junctin. Mutation in these proteins results in misfolding or malfunction of these proteins, thereby affecting their Ca2+-binding affinity, and subsequently disturbs Ca2+ homeostasis during excitation–contraction coupling (E-C coupling). Furthermore, transient disturbance of Ca2+ homeostasis increases membrane potential and causes Ca2+ store overload-induced Ca2+ release, which in turn leads to delayed after depolarization and arrhythmia. Previous studies have focused on the interaction between ryanodine receptors and protein kinase or phosphatase in the cytosol. However, recent studies showed the regulation signaling for ryanodine receptor not only from the cytosol but also within the SR. The changing of Ca2+ concentration is critical for protein interaction inside the SR which changes protein conformation to regulate the open probability of ryanodine receptors. Thus, it influences the threshold of Ca2+ released from the SR, making it easier to release Ca2+ during E-C coupling. In this review, we briefly discuss how Ca2+ handling protein variations affect the Ca2+ handling in CPVT.